Indonesian Banking Financial Performance on Profitability Using Panel Data Regression - Afriansyah, Riki; Pidaryani; Pratama, Muhammad Setya (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
This study's goal is to determine if the return on assets (ROA) variable posted on the Indonesia Stock Exchange, together with the loan-to-deposit ratio (LDR), capital adequacy ratio (CAR), and non-performing loans (NPL), are correlated with profitability. The impact of return on assets (ROA) factors on the banking sector is investigated in this study. The research used a data sample of 245 from 49 financial institutions that have continuously fulfilled the necessary data requirements for a minimum of five years. Panel data, testing of panel data, testing of classical assumptions, and multiple regression analysis employing econometric views (E-views 12) are among the chosen analytical techniques. The ROA variable is unaffected by the LDR variable's t-test findings. In a similar vein, the ROA variable is unaffected by the t-test findings for the CAR variable. Moreover, the ROA variable is unaffected by the NPL variable's t-test findings. Nonetheless, the ROA variable is concurrently impacted by the LDR, CAR, and NPL factors.